Suitable Binary and Ternary Thermodynamic Conditions for Hydrate Mixtures of CH4, CO2, and C3H8for Gas Hydrate-Based Applications - Nallakukkala, S. (American Chemical Society, 2022)
The selection of suitable hydrate formers and their respective gas composition for high hydrate formation, driving force is critical to achieve high water recovery and metal removal efficiency in the hydrate-based desalination process. This study presents a feasibility analysis on the possible driving force and subcooling temperatures for the binary and ternary mixtures of methane, carbon dioxide, and propane for hydrates-based desalination process. The driving force and subcooling for the gas systems was evaluated by predicting their hydrate formation phase boundary conditions in 2 wt NaCl systems at pressure ranges from 2.0-4.0 MPa and temperatures of 1-4 °C using modified Peng-Robinson equation of state in the PVTSim software package. The results suggest that the driving force of CH4+ C3H8and CO2+ C3H8binary systems are similar to their ternary systems. Thus, the use of binary systems is preferable and simpler than the ternary systems. For binary gas composition, CO2+ C3H8(70:30) exhibited a higher subcooling temperature of 8.07 °C and driving force of 1.49 MPa in the presence of 2 wt aqueous solution. In the case of the ternary system, CH4-C3H8-CO2gas composition of 10:80:10 provided a good subcooling temperature of 12.86 °C and driving force of 1.657 MPa for hydrate formation. The results favor CO2-C3H8as a preferred hydrate former for hydrate-based desalination. This is attributed to the formation of sII structure and it constitutes 136 water molecules which signifies a huge potential of producing more quantities of treated water. © 2022 American Chemical Society. All rights reserved.